ANALISIS KANDUNGAN ANTIOKSIDAN DAN MINERAL KALSIUM (Ca), KALIUM (K), DAN BESI (Fe) DARI EKSTRAK BUAH JAMBU AIR (Syzygium samarangense) VARIETAS MADU DELI HIJAU (MDH) - Sri Pratiwi Aritonang (Universitas Methodist Indonesia, 2018)
It has been done research on the antioxidant activity assay from ethyl acetate extracts of guava fruits varieties green deli honey against free radical DPPH (1,1-Diphenyl-2-Picrylhdrazyl) and The mineral content such as Calcium (Ca), Potassium (K), and Iron (Fe) by visible spectrophotometric visible at 516.5 nm wavelength. As a comparison used antioxidant vitamin C (positive control). The guava fruits were extracted by soxhletation using ethyl acetate solvent for 24 hours while for the test of secondary metabolite compound with phytochemical screening. The extracts contain phenol compound group of flavonoida. Antioxidant capability was measured as a decrease in absorbance DPPH solution addition of guava extract. From the results of research showed that antioxidant ethyl acetate extract from guava fruits has IC50 of 446, 7173 mg / L, vitamin C has IC50 2,6583 mg / L. The largest mineral content from guava fruits were Iron (Fe) 6,4892 mg / Kg, Calcium (Ca) 5,6430 mg / Kg, and Potassium (K) 3,2466 mg / Kg.